Frequency Interference Analysis and Calculation of Geostationary-Orbit Satellite Network - Chang LIU; Wenkang WEI; Wei LI (天地一体化信息网络)
The status of the submission and coordination of the global geostationary-orbit (GSO) satellite networks, GSO satellites in orbit were reviewed.The international rules of interference analysis and calculation between GSO satellite networks, two calculation methods of judging whether the coordination was needed coordination arc and ΔT/T, the calculation method of C/I and the access of the input parameters under diff erent scenarios were studied.The softwares of Visualyse GSO and ITU GIBC were introduced.The interference using the Visualyse GSO software between GSO satellite networks with different orbital separations was analyzed.It provides a reference for satellite operators to analyze and calculate the interference between GSO satellite networks and ensure the practical availability of satellite frequencies.